Metode Pembentukan Karakter Pada Anak Usia Dini - Rahmadi Ali; Rahmadi Nurdalila; Sulaiman Sulaiman; Anggriani Anggriani (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
The purpose of this service activity is to provide information to parents, PAUD teachers about methods of character building in children. Character building is very effective starting from an early age, because early childhood still has an imitation spirit, meaning that if given a good example, it will be good too. The targets to be achieved after the implementation of this activity are parents and PAUD teachers so that character building must begin when children are at an early age. The method in this service activity is the lecture method and interactive question and answer with partners. Overall this service activity went smoothly and received a good response from parents and teachers. The majority of participants hoped that this activity would not stop there, but that there would be more intensive follow-up. With this activity, PAUD parents and teachers get information about methods for character building, so they can do it themselves at home. Keywords: Method, character building, early childhood